Comprehensive Pan-Cancer Analysis and Functional Studies Reveal SLC2A6 as a Ferroptosis Modulator in Hepatocellular carcinoma - Guohong Yan; Hailian Huang; Ziyan Lu; Meifeng Chen; Xiang Wang; Pei Zhong; Chongjiu Qin; Shutian Mo; Chuangye Han; Xiaoling Luo; Xinping Ye (Scientific Reports)
Abstract Soluble vector family member 6 (SLC2A6) has been implicated in the aggressiveness and poor prognosis of various cancers, yet its specific role in hepatocellular carcinoma (HCC) remains to be fully elucidated. This study utilized multiple databases to investigate the relationship between SLC2A6 expression and clinical stage, methylation status, drug sensitivity, immune infiltration, and immune checkpoint regulation. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted. Furthermore, in vitro and in vivo experiments were performed to assess the impact of SLC2A6 knockout on the proliferation, migration, invasion, and underlying mechanisms in hepatocellular carcinoma (LIHC) cells. SLC2A6 expression was significantly correlated with tumor prognosis, clinical stage, and methylation levels, and was found to influence immune cell infiltration and immune checkpoint gene expression. In LIHC, SLC2A6 was associated with key biological processes, including the cell cycle, P53 signaling, and ferroptosis. Knockdown of SLC2A6 markedly suppressed the proliferation, migration, and invasion of HCC cells, with this inhibition being closely tied to the ferroptosis pathway. SLC2A6 plays a pivotal role in the regulation of pan-cancer processes, particularly in tumor prognosis and immune-related mechanisms. In LIHC, it emerges as a potential prognostic biomarker and therapeutic target for the regulation of ferroptosis, offering new insights for targeted cancer therapies.